Передумови формування та реалізації стратегії інноваційного розвитку підприємств сфери торгівлі - Попадинець, Н. М.; Papadynets, N. M. (Видавництво Львівської політехніки, 2017)
Досліджено теоретико-методологічні засади формування і реалізації стратегії інноваційного розвитку підприємств сфери торгівлі. Виділено елементи інноваційної стратегії розвитку підприємств сфери торгівлі. Визначено складові механізму реалізації стратегії інноваційного розвитку підприємств сфери торгівлі. Запропоновано механізм формування стратегії інноваційного розвитку підприємств сфери торгівлі. Доведено, що за вибору інноваційної стратегії розвитку підприємств сфери торгівлі необхідно орієнтуватися не тільки на досягнення потенційно можливих абсолютних показників, але й на власну технологічну базу

Development of modern society is characterized by accelerated growth of services sphere contributing to meeting material and spiritual needs of society, efficient use of leisure time and personal fulfillment. Differentiation of services sphere is significant enough. Large, medium, small and microenterprises in the trade branch take considerable share in this sector. Trade companies have the leading place in economic complex of the country, because significant number of employed in the economy of the country works in this sphere. The article aims to research theoretical and methodological foundations of forming and implementation of trade sphere enterprises’ innovative development strategy. The article examines theoretical and methodological foundations of forming and implementation of trade sphere enterprises’ innovative development strategy. On the basis of this research generalization the authors emphasizes the fact that innovative development strategy is the way to manage trade enterprise, which finds and implements its innovative capacity on the basis of internal and external environment condition evaluation, achieving sustainable development in short-term and long-term periods. The following preconditions of forming of trade enterprises innovative development strategy are outlined: 1) lack of efficient owners. This leads to the fact that enterprises’ major operating objective reduces exclusively to obtainment of profits without taking into account the strategic development of enterprises; 2) lack of systemic approach in management due to which domestic enterprises remain to be focused on own capacity basing on their internal sources. Introduction of scientific and technical achievements predominantly takes place through purchase of materialized technologies; 3) conflict of management and owners interests regarding the defining of ways and methods of objectives accomplishment within the limits of a strategy; 4) lack of qualification of management staff, preventing them from defining of major innovative development directions. The elements of trade sphere enterprises’ innovative development strategy are outlined. The components of the mechanism trade sphere enterprises’ innovative development strategy implementation are defined as following: administrative, legal and economic means; innovative structure and its components; elaboration of innovative activity development concept; production and technology component (business incubators, scientific centers); forming of regulative basis; staff (training of staff for innovative activity); promotion of innovation projects (reduced taxes, loans); consulting (economic, technological, marketing consulting); integration of scientific institutions’ and higher educational establishments’ activity; informational (connection, Internet, system of scientific and technical information); management of innovative process; financial component (development funds, non-budgetary funds). The mechanism of forming of trade sphere enterprises’ innovative development strategy is suggested and major factors of its forming process are outlined. The fact that it is important to consider not only the achievement of potentially possible absolute parameters, but also own technological basis, while choosing the trade sphere enterprises’ innovative development strategy is emphasized. Neglect of this factor in the course of innovative strategies forming can lead to failure to achieve the desired efficiency level.
Preconditions of forming and implementation of enterprises’ innovative development strategy in the trade activity field
Keywords: інновації; механізм; стратегія; підприємства; розвиток; сфера торгівлі; innovations; mechanism; strategy; enterprises; development; the sphere of trade; 339.37; 330.3; 330.341.1